PENGARUH SUBSTITUSI UBI JALAR UNGU DAN PISANG KEPOK TERHADAP SIFAT ORGANOLEPTIK DAN SERAT PANGAN FLAKES SEBAGAI ALTERNATIF PANGAN FUNGSIONAL PENCEGAH OBESITAS - Ghaizani Nabaa Pertiwi (2020)
The prevalence of obesity in Indonesia from year to year is increasing, obesity can be prevented by eating foods which are high in fiber. The objective of the study was to analyze the effect of substitution of purple sweet potato and kepok banana on organoleptic test and dietary fiber content of flakes as an alternative functional food prevention of obesity. This study used a completely random eksperimental designed with one factor using four level of treatments, was assigned of wheat flour, purple sweet potato flour, and kepok banana flour F0 (100%:0%:0%), F1 (50%:25%:25%), F2 (40%:30%:30%) and F3 (30%:35%:35%). Organoleptic and dietary fiber content data were analyze using Kruskall Wallis test and ANOVA test. The organoleptic test result shows which, there's significant effect (p<0,05) of purple sweet potato and kepok banana substitution decreased levels panelists preference for texture aspect of flakes. Based on dietary fiber content test, the result shows which, there's significant effect (p<0,05) on purple sweet potato and kepok banana substitution increased levels to dietary fiber content of flakes. The best treatment was flakes with wheat flour, purple sweet potato flour, and kepok banana flour (30%:35%:35%). Flakes with this formulation were mostly accepted by panelists and had serving size nutition information (35 gram) which are the energy (6,54%), protein (3,87%), fat (1,81%), carbohydrate (9,26%) and dietary fiber (14,46%).